Modelling water systems in an introductory undergraduate course: Students' use and evaluation of data-driven, computer-based models. Issue 14 (22nd September 2019) - Lally, Diane; Forbes, Cory
ABSTRACT: Introductory undergraduate courses present an opportunity to use disciplinary concepts in solving authentic problems. Making complex natural systems accessible to students through computer-based models allows them to practice making evidence-based predictions and communicate understanding. Despite the importance of modelling tools in formal classrooms, gaps exist in our understanding of how post-secondary students engage in computer-based modelling. Introductory courses, particularly in the hydrosciences, typically do not use these tools. This mixed methods study examines students' model-based reasoning about a water-related issue over two years in response to a flipped course model. Students in an introductory water course learned basic hydrologic content and used a computer-based water model to complete a project. Data came from a pre-/post-course assessment, student assignments, and student interviews. Results of quantitative and qualitative data analyses show that students in the revised version of the course (Year 2, n = 53) increased their understanding of core hydrology concepts and performed better on their evaluation of a computer-based water model, than students in the initial course (Year 1, n = 38). We tentatively attribute these observed changes to increased active learning opportunities surrounding computer-based modelling of water systems. Findings contribute to science literacy development, undergraduate science learning environment design, and undergraduate scientific modelling.